ENT manifestation in children with Eosinophilic Esophagitis - Bento, Margarida Lagarto (2020)
Objective: Characterize a population of children with Eosinophilic Esophagitis (EoE), highlighting their symptoms, ENT physical examination and previous medical history.  Material and Methods: Cross-sectional observational study of children aged 6 to 17 years, diagnosed with EoE, until January 2019. A clinical observation protocol was applied to every child.  Results: Fifteen children were included. The majority had nasal symptoms (93,3%) and/or pharyngolaryngeal symptoms (80%). Ear complaints were present in 40% of the children. The majority were submitted to flexible nasal endoscopy (73,3%) and 33,3% had indirect signs of laryngopharyngeal reflux. Before this study, 40% of the children had already been observed by an ENT doctor. Atopy was present in 80% of the children.  Conclusions: The ENT’s role in the management of children with EoE may be to consider this diagnosis, to treat ENT manifestations and to identify patients with atopy and laryngopharyngeal reflux who need management by other specialities.